Incidence of Hippocampal Metastases: Laterality and Implications for Unilateral Hippocampal Avoiding Whole Brain Radiotherapy - Kazda, Tomas; Misove, Adela; Burkon, Petr; Pospisil, Petr; Hynkova, Ludmila; Selingerova, Iveta; Dziacky, Adam; Belanova, Renata; Bulik, Martin; Rehak, Zdenek; Poprach, Alexandr; Slama, Ondrej; et al. (BioMed research international, 2018)
Introduction: Hippocampi sparing whole brain radiotherapy (WBRT) is an evolving approach in the treatment of patients with multiple brain metastases, pursuing mitigation of verbal memory decline as a consequence of hippocampal radiation injury. Accumulating data are showing different postradiotherapy changes in the left and right hippocampus with a theoretical proposal of only unilateral (dominant, left) hippocampal sparing during WBRT. Method: The aim of this retrospective study is to describe spatial distribution of brain metastases on MRI in a cohort of 260 patients (2595 metastases) and to evaluate distribution separately in the left and right hippocampus and in respective hippocampal avoiding zones (HAZ, region with subtherapeutic radiation dose), including evaluation of location of metastatic mass centre. Results: The median number of brain metastases was three, with lung cancer being the most common type of primary tumour; 36% had single metastasis. Almost 8% of patients had metastasis within hippocampus (1.1% of all metastases) and 18.1% of patients within HAZ (3.3% of all metastases). No statistically significant difference was observed in the laterality of hippocampal involvement, also when the location of centre of metastases was analyzed. There were more patients presenting the centre of metastasis within left (15) versus right (6) HAZ approaching the borderline of statistical significance. Conclusion: No significant difference in the laterality of BM seeding within hippocampal structures was observed. The hypothesized unilateral sparing WBRT would have theoretical advantage in about 50% reduction in the risk of subsequent recurrence within spared regions.
Keywords: Hippocampus; mužské pohlaví; lidé středního věku; nádory mozku; Middle Aged; ženské pohlaví; Neoplasm Metastasis; hipokampus; Male; Female; lidé; Humans; Retrospective Studies; Organ Sparing Treatments; metastázy nádorů; léčba šetřící orgány; Brain Neoplasms; retrospektivní studie